Esterifikasi asam lemak bebas dalam minyak sawit mentah untuk produksi metilester - Prakoso, Tirto; Kurniawan, Indra B; Nugroho, R Heru (Jurnal Teknik Kimia Indonesia, 2007)
Methyl esters are one of alkyl esters compound that used as alternative diesel fuel became popular. Methyl esters have similarities on physical and chemical properties with the diesel fuel produced from fossil oil; however it has less combustion and environmental emissions. As fossil oil become rare to be exploited, and the rapid environmental issues, the efforts to develop methyl esters as alternative diesel fuel become a prospective one. One method to produce methyl esters from free fatty acids of crude palm oil (CPO) is the two step esterification-transesterification reaction, each step produce the same final product, however differs in the side product. Esterification produce water and transesterfication produce glycerin. The reaction uses alcohol as main reactant beside the free fatty acids, it can be conducted in batch or continuous production. In this research, the investigation is only emphasized in the first step that is the esterification step to produce methyl esters from free fatty acids contained in crude palm oil. Methanol and sulfuric acid are used as reactant and catalyst respectively. Methyl esters produced by esterification is affected by reaction temperature, amounts of catalyst, and methanol volume. The increase in temperature improved esterification conversion from 19% in 50C to 98% in 60C. While the usage of the highest amount of catalyst, 5 ml/1-CPO, led to produced the highest conversion relative to the conversion from 1 and 3 ml/1-CPO catalyst. Furthermore, 10% amount of methanol per volume CPO produced higher yield than 8%.Keywords : Biodiesel, Â CPO Free Fatty Acid Esterification, Methyl Ester ConversionAbstrakÂ Metil ester merupakan suatu senyawa alkil ester yang dapat digunakan sebagai bahan bakar alternatif. Metil ester memiliki sifat fisik dan kimia yang hampir sam a dengan minyak diesel yang dihasilkan dari minyak bumi tetapi emisi pembakaran dari penggunaan ester metal lebih rendah dari pada emisi hasil penggunaan minyak solar. Seiring dengan semakin langkanya sumber minyak bumi dan semakin gencarnya isu lingkungan hidup, pengembangan ester metil sebagai bahan bakar pengganti minyak solar semakin prospektif. Pembuatan ester metil dari asam lemak bebas minyak sawit mentah (crude palm oil) dapat dilakukan dengan beberapa cara antara lain dengan reaksi esterifikasi dan transesterifikasi menggunakan alkohol. Reaksi-reaksi ini dapat dilaksanakan secara batch maupun kontinu. Pada penelitian yang telah dilakukan, pembuatan ester metil dari asam lemak bebas minyak sawit mentah dilakukan dengan reaksi esterifikasi secara batch, dengan reaktan berupa minyak sawit mentah dan metanol. Katalis yang digunakan adalah H2SO4. Konversi ester metil yang dihasilkan dipengaruhi oleh temperatur reaksi, konsentrasi katalis dan konsentrasi metanol. Kenaikan temperatur reaksi akan meningkatkan konversi dari 19% pada 50oC menjadi 98% pada 60oC. Dengan menggunakan konsentrasi katalis tertinggi 5ml/l CPO memicu konversi tertinggi relatif dibandingkan nilai konversi dari 1 dan 3 ml/l CPO. 10% metanol menghasilkan perolehan tinggi dibanding 8%.Kata Kunci: Biodiesel, EsterifikasiAsam Lemak Bebas CPO, Konversi Ester Metil